Design System of Internal Financial Report Applications (Case Study: Lppm UPN - Putra, C. A.; M. Idhom (Future Science)
Institution of Research and Community Service (LPPM) is an institution that manages research and community service activities at University of Pembangunan Nasional “Veteran” Jawa Timur. Research and community service management activities in universities are accommodated by a system that regulates the flow of research and community service financial reporting. The system is called SIRIP. This system can also display report information to its users. Purpose of this research is to create a system that is capable of managing financial reporting activities and financial recapitulation on research and community service at University of Pembangunan Nasional “Veteran” Jawa Timur. In designing this web-based systems, author using Rapid Application Development (RAD) as method. RAD is an object-oriented approach to system development which includes development methods and software. This financial report management system is called SIREKAP. LPPM and Lecturers as users of this system, can report financial recapitulation using this system. This system is designed according to requests from users. Results of this information system design make it easier for officers to process data. Other result are can also facilitate, accelerate and can save time in reporting management. SIREKAP is used to recapitulate financial reports on research activities and community service.